슈의 팽화에 대한 저온 조건의 영향 - 김명애; Myoung Ae Kim (Journal of the Korean Society of Food Culture, 2018)
This study examined the effects of low temperature conditions on the expansion of choux when mixing the dough with egg fluid. The egg fluid was tested at 5 and 17oC, and the dough temperature was 20, 30, 40, 50, 60 or 70oC. The expansion decreased with decreasing temperature of the egg fluid and dough, with the concomitant formation of membranes in the cavities of choux because of the poor emulsion stability of the choux paste. In addition, the structure of the choux pastry was not dense and the cracks in the surface were partial and narrow. The shape, expansion and cracks of choux were the best at a dough temperature of 60 and 70oC added with egg fluid at 17oC. The temperature of the choux paste in these two samples was higher than the melting point of the butter used to produce the paste. Therefore, the practical limit temperature when mixing the egg fluid and dough is 20 and 60oC, respectively, and care should ve taken to maintain a low temperature when making choux in confectionary.